Pembinaan Pengawas Melalui Kelompok Kerja Guru Pendidikan Agama Islam untuk Meningkatkan Keterampilan Mengajar - Sofiah Sofiah; Sofyan Sauri; Marwan Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The performance problems of Islamic religious education teachers in an effort to improve the quality of the learning process according to legislation such as the implementation of monotonous learning, teachers do not use learning media, low teacher performance motivation. This study aims to identify and analyze the planning, implementation, organization, evaluation as well as the obstacles and solutions faced in the development of supervisors through the working group of Islamic religious education teachers to improve teaching skills. The research method used is descriptive qualitative. The results of the study found that supervisory development through teacher working groups to improve teacher skills was in accordance with the supervisory development function which included planning, implementation, evaluation and components that were directly involved. Natural barriers include supervisor figures who have limited time intensity, the number of school locations that must too many targeted areas were visited. The solution to minimize obstacles was carried out for supervisory figures by scheduling coaching in collaboration with the working group organization of Islamic religious education teachers.